MENINGKATKAN HASIL BELAJAR SISWA KELAS IX C MENGGUNAKAN STRATEGI PEMBELAJARAN BERBASIS MASALAH DALAM PEMBELAJARAN IPS MATERI PERDAGANGAN INTERNASIONAL TAHUN AJARAN 2018/2019 DI SMPN 21 TANJUNG JABUNG TIMUR - Dwi Nanda Akhmad Romadhon (Universitas Batanghari Jambi, 2018)
Abstract One of the economic material is about economic cooperation between countries. The standard function of the educational process as a tool to achieve educational goals, one indicator of success in implementing the learning process. The achievement of learning outcomes is influenced by various factors. One of the factors is the social studies learning process of class IX, especially in class IX C of Tanjung Jabung Timur Junior High School 21 which is still unable to achieve the learning outcomes to be achieved. The conditions that occur at Tanjung Jabung Timur Junior High School 21 in class IX C reach the minimum completeness criteria (KKM) 77, only 29% of 34 students, this condition is caused by students not being able to reach the learning process, due to the lack of teachers developing a rudimentary learning process. Therefore the research problem is formulated as follows; is